(3GdQSGdI GdgGOjIs - (3eMeO Hf ESMGb Hf eMeO Hf jhSa Hf Ydj Gdbhfhj GdQhej, UOQ GdOjf,J (B673 (3g` s
(3ChdgG (B:s
(3GdOGYi GdeNdU GdabjQ eMeO Hf ESMb TYQ eGRGd SeYi jYi efg WjH PcQc eG Hg PQ Ydi GdQhV ZH GdYGQV s
(3BNQgG (B:s
(3hGddg SHMGfg jRjd HfhQ EQTGOg Xde GdTchc GdOhGeS hjHbjI QcfkG jdLC Zdjg hfbhd ai cTa cd eYVdI Ydjg hGdSdGe JeJ GdQSGdI GdgGOjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B30s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B900s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs